2015
DOI: 10.5152/anatoljcardiol.2015.6122
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate recovery, cardiac rehabilitation and erectile dysfunction in males with ischaemic heart disease

Abstract: Objective:Heart rate recovery (HRR) is a recognised marker used in clinical practice for assessing the risk of sudden cardiac death. Physical exercise leads to an improvement in HRR and has a proven beneficial effect on erection quality (EQ) related to the activity of the autonomic nervous system in men with ischaemic heart disease (IHD). This paper evaluates the relationship between HRR and EQ in patients with IHD and erectile dysfunction (ED) who underwent cardiac rehabilitation.Methods:The main analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
(53 reference statements)
1
15
0
1
Order By: Relevance
“…The ED score was “mild” at baseline for the intervention and control groups in 5 studies ( Table 3 ). In contrast to the control groups, the intervention groups in the 3 studies by Kalka et al 51 , 52 , 53 achieved an improvement of erectile function, which remained in the category “mild.” In Maio et al 47 and Khoo et al, 48 the control groups also achieved an improvement in erectile function, but the improvement of the control groups was not as high as in the intervention groups.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…The ED score was “mild” at baseline for the intervention and control groups in 5 studies ( Table 3 ). In contrast to the control groups, the intervention groups in the 3 studies by Kalka et al 51 , 52 , 53 achieved an improvement of erectile function, which remained in the category “mild.” In Maio et al 47 and Khoo et al, 48 the control groups also achieved an improvement in erectile function, but the improvement of the control groups was not as high as in the intervention groups.…”
Section: Resultsmentioning
confidence: 89%
“…After examining the full texts of these articles, 42 studies were excluded because the requested data were not reported, leading to the inclusion of 10 studies. 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55
Figure 1 Flowchart of data collection process. IIEF = International Index of Erectile Function.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations